2020
DOI: 10.1093/jas/skaa082
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the ratio of SID lysine to metabolizable energy improves pig performance during a viral challenge

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) compromises pig performance. However, increasing standardized ileal digestible Lys per Mcal metabolizable energy (SID Lys:ME) above requirement has been shown to mitigate reduced performance seen during a porcine reproductive and respiratory syndrome (PRRS) virus challenge. The objective of this study was to evaluate the effects of increasing the dietary SID Lys:ME from 100% National Research Council (NRC) requirement to 120% of the requirement in vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
4
6
0
Order By: Relevance
“…In pigs, feeding a high fiber diets normally has negative effects on voluntary feed intake, as high fiber diets decrease the rate of gastric emptying, thus contributing to earlier satiety (Kerr and Shurson, 2013). However, in the current study, similar to results reported by Jasper et al (2020), overall ADFI increased 8.6% in HF fed PRRSV challenged pigs (Exp. 1).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In pigs, feeding a high fiber diets normally has negative effects on voluntary feed intake, as high fiber diets decrease the rate of gastric emptying, thus contributing to earlier satiety (Kerr and Shurson, 2013). However, in the current study, similar to results reported by Jasper et al (2020), overall ADFI increased 8.6% in HF fed PRRSV challenged pigs (Exp. 1).…”
Section: Discussionsupporting
confidence: 78%
“…Lys intake), as reductions in ADFI are typically reported in PRRSV challenged pigs . The beneficial performance reported when increasing dietary Lys:ME in PRRSV challenged pigs has been further validated by our group (Jasper et al, 2020) utilizing two formulation approaches;…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations